Review of Self-directed Learning Readiness Assessments Among Undergraduate Students in the World and Lessons Learnt for Vietnam - Thuy, Dang Thi Thanh; Thuy, Tang Thi; Minh, Trinh Van (VNU Journal of Science: Education Research, 2021)
This article aims to provide the selected findings of self-directed learning readiness assessment to undergraduate students in various countries. It also offers relevant recommendations for promoting self-directed learning to Vietnamese higher education institutions. Through desk study by analyzing articles and studies of self-directed study readiness assessment, the result shows that the level of self-direct learning readiness among undergraduate students is different due to the influence of mental, social and demographic variables. Some practical recommendations for higher education institutions, students, teachers and researchers are proposed to promote self-directed learning. It is expected that this study will partly contribute to promote the students’ initiative and creativity in learning associated with lifelong learning.